Does Congress Still Care about Fraud, Waste, and Abuse: Yes, A Descriptive Analysis of Bills and Hearings, 1993–2016. (4th March 2021) - Brown, Heath
Abstract : Public administration scholars have taken up the study of fraud, waste, and abuse, but typically from an executive or bureaucratic perspective. The aim of this paper is to deepen what we know about the topic by re-orienting the focus back to Congress, in line with Paul Light's seminal book on the subject. By examining two decades of Congressional bill and hearings data, the findings show Congress has remained active on fraud, waste, and abuse, but no single theory of legislative behavior best explains the patterns of activity